DIGITAL ENTREPRENEURSHIP STRATEGY IN ONLINE BUSINESS COMPANIES IN WEST JAVA - Anton Priyo Nugroho; Norvadewi Norvadewi; Murwani Wulansari; Farida Akbarina; Muhammad Yusuf (Universitas 17 Agustus 1945 Semarang, 2023)
The goal of this study is to ascertain how digital entrepreneurship strategies are applied by online business organizations in West Java from an Islamic perspective. This is a field research with a qualitative approach and descriptive qualitative approaches. Data were gathered through interviews, observations, documentation, and literature searches. Data analysis approaches make use of inventory or data collection, identification, analysis, and interpretation. The study's conclusions show that the four tenets of client orientation, transparency, fair competition, and fairness serve as the foundation for the digital entrepreneurship strategy employed by online business firms in West Java. The customer-oriented philosophy is first put into practice by providing polite, soft, and friendly service and by always being prepared to offer solutions. Second, the concept of openness is put into practice, and product specifications are truly communicated. Third, the idea of fair competition is put into practice through prompt delivery, no-cost advice, special offers, and higher-quality products. Fourth, the concept of fairness is put into practice by treating customers fairly and providing them with benefits.